Base-promoted isomerization of CF3-containing allylic alcohols to the corresponding saturated ketones under metal-free conditions - Hamada, Yoko; Kawasaki-Takasuka, Tomoko; Yamazaki, Takashi (Beilstein Journal of Organic Chemistry, 2017)
Following to the computational expectation, our previously reported intriguing 1,3-proton shift of 4,4,4-trifluorobut-2-yn-1-ols was successfully extended to the 4,4,4-trifluorobut-2-en-1-ol system under metal-free conditions to afford the corresponding saturated ketones in high to excellent chemical yields using such a convenient and easy-to-handle base as DBU at the toluene refluxing temperature, and utilization of the corresponding optically active substrates unambiguously demonstrated that this transformation proceeded in a highly stereoselective fashion.
Keywords: allylic alcohols; chirality; computation; 1,3-proton shift; trifluoromethyl

(untitled) - Yamazaki, T.; Kawasaki-Takasuka, T.; Furuta, A.; Sakamoto, S. (Tetrahedron, 2009)

(untitled) - Watanabe, Y.; Yamazaki, T. (J. Org. Chem., 2011)

(untitled) - Jiang, Z.-X.; Qing, F.-L. (J. Fluorine Chem., 2003)

(untitled) - Tiruveedhula, V. V. N. P. B.; Witzigmann, C. M.; Verma, R.; Kabir, M. S.; Rott, M.; Schwan, W. R.; Medina-Bielski, S.; Lane, M.; Close, W.; Polanowski, R. L.; Sherman, D.; Monte, A.; et al. (Bioorg. Med. Chem., 2013)

(untitled) - Wang, Y.-H.; Liu, H.; Zhu, L.-L.; Li, X.-X.; Chen, Z. (Adv. Synth. Catal., 2011)

(untitled) - Chen, J.; Fan, G.; Liu, Y. (Org. Biomol. Chem., 2010)

Gaussian 09W, Rev. D.01 (Gaussian, 2009)
Full optimization of each species was carried out using the B3LYP/6-311++G** level of theory, followed by the single point calculation using the IEFPCM method for consideration of the solvent effect by THF.

(untitled) - Bizet, V.; Pannecoucke, X.; Renaud, J.-L.; Cahard, D. (Angew. Chem., Int. Ed., 2012)

(untitled) - Bizet, V.; Pannecouocke, X.; Renaud, J.-L.; Cahard, D. (J. Fluorine Chem., 2013)

(untitled) - Wu, M.; Kong, L.; Wang, K.; Jin, R.; Cheng, T.; Liu, G. (Catal. Sci. Technol., 2015)

(untitled) - Xia, X.; Wu, M.; Jin, R.; Cheng, T.; Liu, G. (Green Chem., 2015)

(untitled) - Wu, M.; Kong, L.; Wang, K.; Jin, R.; Cheng, T.; Liu, G. (Catal. Sci. Technol., 2015)

(untitled) - Cahard, D.; Bizet, V.; Dai, X.; Gaillard, S.; Renaud, J.-L. (J. Fluorine Chem., 2013)

(untitled) - Ikeda, A.; Omote, M.; Nomura, S.; Tanaka, M.; Tarui, A.; Sato, K.; Ando, A. (Beilstein J. Org. Chem., 2013)

(untitled) - Martinez-Erro, S.; Sanz-Marco, A.; Gómez, A. B.; Vázquez-Romero, A.; Ahlquist, M. S. G.; Martín-Matute, B. (J. Am. Chem. Soc., 2016)

(untitled) - Yamazaki, T.; Mano, N.; Hikage, R.; Kaneko, T.; Kawasaki-Takasuka, T.; Yamada, S. (Tetrahedron, 2015)

(untitled) - Milburn, R. R.; McRae, K.; Chan, J.; Tedrow, J.; Larsen, R.; Faul, M. (Tetrahedron Lett., 2009)

(untitled) - Blanchette, M. A.; Choy, W.; Davis, J. T.; Essenfeld, A. P.; Masamune, S.; Roush, W. R.; Sakai, T. (Tetrahedron Lett., 1984)

(untitled) - Rathke, M. W.; Nowak, M. (J. Org. Chem., 1985)

(untitled) - Takacs, J. M.; Helle, M. A.; Seely, F. L. (Tetrahedron Lett., 1986)